Design and Automation of a PLC-Based Dust Suppression System for Mineral Processing Plants - Moses Kwesi Annan; Isaac Papa Kwesi Arkorful; Ramatu Al-hassan (Applied Engineering, Innovation, and Technology, 2026)
Excessive dust generation in mineral processing and crushing plants poses serious occupational and environmental health challenges. Prolonged exposure to fine particulate matter—particularly Total Suspended Particulates (TSP) and Particulate Matter below 10 µm (PM₁₀)—has been linked to respiratory diseases and reduced air quality in surrounding areas. Dust concentration data collected over a nine-year period revealed that approximately 20 % of TSP values exceeded the 150 µg/m³ safety limit, while 25 % of PM₁₀ readings surpassed the 70 µg/m³ threshold, with peak levels reaching over 300 µg/m³ during dry months. These findings underscore the need for continuous and responsive dust control in processing environments. This study presents the design and simulation of an automated dust suppression system using a Programmable Logic Controller (PLC) integrated with dust and water-level sensors. Developed in RSLogix 500 and visualized in LabVIEW, the system automatically detects hazardous dust levels and activates low-pressure water spray nozzles in 15-second suppression cycles, with dust concentration re-checked after each cycle until levels fall below safe thresholds. MATLAB was employed to analyze nine years of historical dust concentration data and establish the threshold parameters used to configure the PLC control logic. Simulation results demonstrate reliable real-time monitoring, automated threshold-triggered suppression, and elimination of manual intervention in dust concentration control. The proposed automation framework provides a scalable solution for improving air-quality compliance, worker safety, and operational efficiency in mineral processing facilities.